2016
DOI: 10.4209/aaqr.2015.03.0197
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Hydrocarbons and Halocarbons at a Mountaintop in Southern China

Abstract: In this study, 45 ambient samples were collected in the summer of 2011 and spring of 2012 on Mount Lushan. The concentrations and seasonal distributions of aromatic hydrocarbons and halocarbons were measured and discussed. Moderate concentrations of individual species were found compared with other mountain sites; however, the measured concentrations were much lower than the values reported in cities. For aromatic hydrocarbons, benzene and m/p-xylene were the most abundant species in the spring, while benzene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Ozone is a secondary pollutant that is generated in photochemical reactions which are often more toxic than (Yang et al, 2016). Table 4 lists speciated VOCs and their OFPs.…”
Section: Analysis Of Ozone Formation Potentialmentioning
confidence: 99%
“…Ozone is a secondary pollutant that is generated in photochemical reactions which are often more toxic than (Yang et al, 2016). Table 4 lists speciated VOCs and their OFPs.…”
Section: Analysis Of Ozone Formation Potentialmentioning
confidence: 99%
“…The outdoor levels of p-DCB range from 0.01 to 1 ppb and are much lower than its indoor levels (ATSDR, 2006). More recently, Yang et al (2016) reported summertime concentrations of 0.60, 0.02, and 0.08 ppb for R-150, R-150a, and p-DCB, respectively, at the top of Lushan, a mountain in China. Although R-150, R-150a, and p-DCB have been observed in both background and urban atmosphere, no reliable estimates of their global emissions or inventories are available to date (Carpenter et al, 2014).…”
Section: Halocarbonsmentioning
confidence: 99%
“…Measurements have been obtained using aircrafts (Blake et al, 1996;Bechara et al, 2008;Baker et al, 2010) and tethered balloons (Helmig et al, 1998;Spirig et al, 2004) operated at different heights. Ground-based measurements of VOCs at high-altitude stations have also been conducted in various locations, such as North America (Swanson et al, 2003;Khwaja and Narang, 2008;Burley et al, 2016), Europe (Karl et al, 2001;Li et al, 2005;Helmig et al, 2008;Lanz et al, 2009;Lo Vullo et al, 2016a, b), Africa (Schmitt and Volz-Thomas, 1997), East Asia (Sharma et al, 2000;Suthawaree et al, 2010;Xue et al, 2013;Yang et al, 2016), and Hawaii (Greenberg et al, 1992(Greenberg et al, , 1996 the Japan Meteorological Agency (JMA). Yearlong and multiple-year measurements of tropospheric ozone Dokiya et al, 2001), water-soluble ions from aerosol samples (Suzuki et al, 2008), and rainwater ) have been successfully obtained at the FRS.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the analytical procedures of VOCs have been described previously by Yang et al (2016) and will be described here briefly.…”
Section: Sample Analysismentioning
confidence: 99%
“…Research on VOCs in the high mountains is of great significance to the study of global temporal and spatial variation of VOCs. Studies now have been performed on the concentration characteristics, seasonal and diurnal variations and source identification of VOCs at the summit of some mountains in China (Tang et al, 2007;Tang et al, 2008;Zhang et al, 2014;Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%